2011
DOI: 10.3844/ajebasp.2011.498.505
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation of Emergency Department at a Teaching Hospital in Tehran University of Medical Sciences in 2010

Abstract: Problem statement:Considering the importance of emergency departments in healthcare system and the high mortality rate of patients referred to these departments, it is crucial to provide quality services in emergency departments. Accreditation is a systematic process for improving quality of care and it enables managers to assess and evaluate the healthcare system. Accreditation of an organization provides an obvious commitment for improving quality of safety, quality of patient care, ensuring safety surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This value was 82.6% in our study [19]. In addition, Farzianpour et al (2010) studied emergency departments of teaching hospitals affiliated to Tehran University of Medical Sciences using health ministry standard questionnaire (9 sets) and JCI based questionnaire and reported a mean score of 86.8% [20]. In our study the mean score in the ACC domain of JCI standards was 82.2% in all departments of the studied hospitals.…”
Section: Hospitals' Accreditationsupporting
confidence: 65%
“…This value was 82.6% in our study [19]. In addition, Farzianpour et al (2010) studied emergency departments of teaching hospitals affiliated to Tehran University of Medical Sciences using health ministry standard questionnaire (9 sets) and JCI based questionnaire and reported a mean score of 86.8% [20]. In our study the mean score in the ACC domain of JCI standards was 82.2% in all departments of the studied hospitals.…”
Section: Hospitals' Accreditationsupporting
confidence: 65%
“…Previous studies in educational evaluation showed average of the function of educational evaluation in basic sciences groups and clinical groups were respectively 76.4 and 86.6% while grand average of the function of clinical groups and basic sciences groups was 80.5% (Farzianpour et al, 2013b;2013c). Rabbani et al (2006) showed general average of the function of internal evaluation in Department of pediatrics faculty of medicine were respectively %53.3 in 2003 and %75.3 in 2004. In university educational system, it is possible to use educational evaluation in electing students, scientific board and curriculum and in general the other educational system inputs in addition, it supervises on system process performing and finally using evaluation directs outputs and system consequences optimally (Farzianpour et al, 2011d).…”
Section: Discussionmentioning
confidence: 99%
“…Standards of Joint Commission International (JCI) emphasize on the organizational performance level in basic functional domains including patient right, patient care, medical safety and infection control. These standards are focused on two principles: Expectations of the actual organizational performance and assessment of organizational capabilities to provide high quality and safe Health Care Services (HCS) (Farzianpour et al, 2011).…”
Section: Introductionmentioning
confidence: 99%